A Novel Combined System of Direction Estimation and Sound Zooming of Multiple Speakers - Khaddour, Hasan; Schimmel, Jiri; Rund, Frantisek (Společnost pro radioelektronické inženýrství, 2015)
This article presents a new system for estimation the direction of multiple speakers and zooming the sound of one of them at a time. The proposed system is a combination of two levels; namely, sound source direction estimation, and acoustic zooming. The sound source direction estimation uses so-called the energetic analysis method for estimation the direction of multiple speakers, whereas the acoustic zooming is based on modifying the parameters of the directional audio coding (DirAC) in order to zoom the sound of a selected speaker among the others. Both listening tests and objective assessments are performed to evaluate this system using different time-frequency transforms.
Keywords: Acoustical zooming; spatial sound; vector base amplitude panning; sound source localization; energetic analysis method; directional audio coding